Vestdijk en de toekomst der religie. Een essay over een essay - Becker, Jos (Religie & Samenleving, 2009)
In 1947 the Dutch literary author Simon Vestdijk published his vision on the religious future of Western Europe. The book, called ‘The future of Religion’, attracted attention. Now that religion gets greater importance in public debate it might be interesting to see if Vestdijk was right. The author predicted the disappearance of Christianity in Western Europe. Other types of religion would inevitably take its place. According to Vestdijk mysticism and socialism would be the religions of the future. Mysticism would appear in the form of Buddhism. Vestdijk regarded socialism as secular religion. Although it is much too early to fully accept the disappearance of Christianity, its decline is unmistakable. This development shows even a higher speed than Vestdijk did imagine 60 years ago. Mysticism in the sense of the individual using his own personality as a means for gaining religious insight has become important. The old socialism with its religious overtones does not exist any longer. However, the idea that the world should be continually improved and that social justice should always and everywhere prevail, seems to be forever present in society. One could with only a few reservations conclude that Vestdijk was in the right on these points.